Mitigating hidden node problem in an IEEE 802.16 failure resilient multi-hop wireless backhaul - Chai, Pey San Nancy (Curtin University, 2011)
Backhaul networks are used to interconnect access points and further connect them to gateway nodes which are located in regional or metropolitan centres. Conventionally, these backhaul networks are established using metallic cables, optical fibres, microwave or satellite links. With the proliferation of wireless technologies, multi-hop wireless backhaul networks emerge as a potential cost effective and flexible solution to provide extended coverage to areas where the deployment of wired backhaul is difficult or cost-prohibitive, such as the difficult to access and sparsely populated remote areas, which have little or no existing wired infrastructure.Nevertheless, wireless backhaul networks are vulnerable to node or link failures. In order to ensure undisrupted traffic transmission even in the presence of failures, additional nodes and links are introduced to create alternative paths between each source and destination pair. Moreover, the deployment of such extra links and nodes requires careful planning to ensure that available network resources can be fully utilised, while still achieving the specified failure resilience with minimum infrastructure establishment cost.The majority of the current research efforts focus on improving the failure resilience of wired backhaul networks but little is carried out on the wireless counterparts. Most of the existing studies on improving the failure resilience of wireless backhaul networks concern energy-constrained networks such as the wireless sensor and ad hoc networks. Moreover, they tend to focus on maintaining the connectivity of the networks during failure, but neglecting the network performance. As such, it calls for a better approach to design a wireless backhaul network, which can meet the specified failure resilience requirement with minimum network cost, while achieving the specified quality of service (QoS).In this study, a failure resilient wireless backhaul topology, taking the form of a ladder network, is proposed to connect a remote community to a gateway node located in a regional or metropolitan centre. This topology is designed with the use of a minimum number of nodes. Also, it provides at least one backup path between each node pair. With the exception of a few failure scenarios, the proposed ladder network can sustain multiple simultaneous link or node failures. Furthermore, it allows traffic to traverse a minimum number of additional hops to arrive at the destination during failure conditions.WiMax wireless technology, based on the IEEE 802.16 standard, is applied to the proposed ladder network of different hop counts. This wireless technology can operate in either point-to-multipoint single-hop mode or multi-hop mesh mode. For the latter, coordinated distributed scheduling involving a three-way handshake procedure is used for resource allocation. Computer simulations are used to extensively evaluate the performance of the ladder network. It is shown that the three-way handshake suffers from severe hidden node problem, which restrains nodes from data transmission for long period of time. As a result, data packets accumulate in the buffer queue of the affected nodes and these packets will be dropped when the buffer overflows. This in turn results in the degradation of the network throughput and increase of average transmission delay.A new scheme called reverse notification (RN) is proposed to overcome the hidden node problem. With this new scheme, all the nodes will be informed of the minislots requested by their neighbours. This will prevent the nodes from making the same request and increase the chance for the nodes to obtain all their requested resources, and start transmitting data as soon as the handshake is completed. Computer simulations have verified that the use of this RN can significantly reduce the hidden terminal problem and thus increase network throughput, as well as reduce transmission delay.In addition, two new schemes, namely request-resend and dynamic minislot allocation, are proposed to further mitigate the hidden node problem as it deteriorates during failure. The request-resend scheme is proposed to solve the hidden node problem when the RN message failed to arrive in time at the destined node to prevent it from sending a conflicting request. On the other hand, the dynamic minislot allocation scheme is proposed to allocate minislots to a given node according to the amount of traffic that it is currently servicing. It is shown that these two schemes can greatly enhance the network performance under both normal and failure conditions.The performance of the ladder network can be further improved by equipping each node with two transceivers to allow them to transmit concurrently on two different frequency channels. Moreover, a two-channel two-transceiver channel assignment (TTDCA) algorithm is proposed to allocate minislots to the nodes. When operating with this algorithm, a node uses only one of its two transceivers to transmit control messages during control subframe and both transceivers to transmit data packets during data subframe. Also, the frequency channels of the nodes are pre-assigned to more effectively overcome the hidden node problem. It is shown that the use of the TTDCA algorithm, in conjunction with the request-resend and RN schemes, is able to double the maximum achievable throughput of the ladder network, when compared to the single channel case. Also, the throughput remains constant regardless of the hop counts.The TTDCA algorithm is further modified to make use of the second transceiver at each node to transmit control messages during control subframe. Such an approach is referred to as enhanced TTDCA (ETTDCA) algorithm. This algorithm is effective in reducing the duration needed to complete the three-way handshake without sacrificing network throughput. It is shown that the application of the ETTDCA algorithm in ladder networks of different hop counts has greatly reduced the transmission delay to a value which allows the proposed network to not only relay a large amount of data traffic but also delay-sensitive traffics. This suggests that the proposed ladder network is a cost effective solution, which can provide the necessary failure resilience and specified QoS, for delivering broadband multimedia services to the remote rural communities.